Cyclodextrin polymers and salts: An Eco-Friendly combination to modulate the removal of sulfamethoxazole from water and its release. (November 2021) - Romita, Roberto; Rizzi, Vito; Gubitosa, Jennifer; Gabaldón, José Antonio; Fortea, María Isabel; Gómez-Morte, Teresa; Gómez-López, V.M.; Fini, Paola; Cosma, Pinalysa
Abstract: This study is aimed to validate water-insoluble cyclodextrin-epichlorohydrin polymer (β-EPI) use to remove, by adsorption, sulfamethoxazole (SMX) from water and then release it via an environmentally friendly treatment so that the adsorbent can be recycled according to one of the objectives of the European Project Life "Clean up" (LIFE 16 ENV/ES/000169). SMX adsorption experiments on β-EPI polymer in-batch were performed, varying different experimental parameters of the process, such as contact time, pH values, and so on. The adsorption process, exothermic and driven by enthalpy, occurs both through the formation of inclusion and association complexes, involves mainly hydrophobic and hydrogen bonds, has a rate-controlling step depending on both pollutant concentration and adsorbent dose and can be described by the Freundlich and Dubinin-Radushkevich models which confirm the polymer surface heterogeneity and the physical nature of the adsorption. The presence of salts gives rise to a general decrease in the SMX sorption, mainly in the case of bromide, which was used to promote the SMX desorption and regenerate the adsorbent. The overall results indicate that β-EPI polymer is not only capable of removing SMX by adsorption with short contact times and a qmax = 10 mg/g but it is also easily regenerated using a 0.5 M solution of sodium bromide without any loss in the adsorption performance and with obvious economic and environmental advantages. The polymer as synthesized, with SMX adsorbed and regenerated was characterized by FT-IR, SEM and DSC. Graphical abstract: Image 1 Highlights: Quick removal of sulfamethoxazole from wastewater by adsorption. Validation of β-EPI polymer as adsorbent material for wastewater treatment plants. Regeneration of β-EPI polymer as adsorption material by a sustainable approach.